2021
DOI: 10.18280/ijdne.160602
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Swamp Microalgal Isolates from South Sumatra as Biofuel Candidates

Abstract: Microalgal isolates in various habitats have different biocomponents, and isolates found in the swamps of South Sumatra have not been explored deeply. This study was designed to analyse morphologically and isolate microalgae that have potential as biofuel candidates through their lipid content. Results showed that five isolates originating from four different sources in South Sumatra, namely, Chlorella vulgaris Beyerinck (DV 005), Dictyosphaerium granulatum Hindák (DV 003), Nannochloropsis sp. (DV 009), Scened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The results of clove oil research conducted by Harni et al [33] in controlling rust disease (Hemileia vastatrix) on coffee leaves showed that clove oil at 5000 µl/L was phytotoxic to coffee leaves. At the same time, Pereira et al [34,35] stated that there were no phytotoxicity symptoms in a similar study due to clove oil (1000 µl/L) application.…”
Section: Discussionmentioning
confidence: 87%
“…The results of clove oil research conducted by Harni et al [33] in controlling rust disease (Hemileia vastatrix) on coffee leaves showed that clove oil at 5000 µl/L was phytotoxic to coffee leaves. At the same time, Pereira et al [34,35] stated that there were no phytotoxicity symptoms in a similar study due to clove oil (1000 µl/L) application.…”
Section: Discussionmentioning
confidence: 87%
“…The fatty acid methyl ester (FAME) was obtained from the transesterification process of triglyceride in the presence of a catalyst. The catalysts existence becomes a significant role since it affects energy needed and cost production [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%